3.
1) x²(x-1) ≠ 0
x ≠ 0, x ≠ 1\
x∈(-∞; 0)U(0; 1)U(1; +∞)
2) 36-x² ≥ 0
36 ≥ x²
-4 ≤ x ≤ 4
x∈[-4; 4]
3)
{3x-2 ≥ 0
{x²-x-2 ≠ 0
{x ≥ 2/3
{(x+1)(x-2) ≠ 0
{x ≥ 2/3
{x ≠ -1
{x ≠ 2
x∈[2/3; 2)U(2; +∞)
4.
1) x²-5x+6 = 0
D = 25-4*6 = 25-24 = 1
x1 = (5-1)/2 = 4/2 = 2
x2 = (5+1)/2 = 6/2 = 3
2) 15/(7x+3)
Данная функция не обращается в нуль, т.к. в числителе константа, а знаменатель не может быть равен нулю.
3) (x²-4x+3)/x-3 = 0
О.О.Ф.: x-3 ≠ 0 => x ≠ 3
x²-4x+3 = 0
D = 16-4*3 = 16-12 = 4
x1 = (4-4)/2 = 0
x2 = (4+4)/2 = 8/2 = 4